Inovasi Alat Pemanggang Berbahan Bakar Elpiji Untuk Rumah Tangga - Awang Surya; Nurkholis Nurkholis; Aji Setyawan; Hilman Sholih (Proceedings Series on Physical & Formal Sciences, 2021)
The most common method used in grilling food is by burning charcoal and food ingredients such as fish and meat, heated from the heat of the charcoal burning. This charcoal grill has the disadvantage that it will produce pollutants into the air. Technically, charcoal grills are more complicated to implement, because during the grilling process the fire must be continuously controlled so that it does not go out. Charcoal grilled food will also get dirty easily. This activity is carried out with the aim of getting a grill design that is easy to operate at home. The method used is engineering research. The activities undertaken are literature study, field observation and design. The result of this activity is the design of a grill that can be operated at home with ease.